Challenges and Strategies in Bridging Aerodynamic Research with Industrial Prototyping: Insights from Formula and Luxury Automotive Design - Zhang, Andi (Simen Owen Academic Proceedings Series, 2026)
This paper investigates the challenges and strategies in bridging aerodynamic research with industrial prototyping, using Formula racing and luxury automotive design as comparative case studies. While Formula cars prioritize downforce, adjustability, and lightweight efficiency, luxury vehicles emphasize low drag, aesthetic integration, and customer perception. The study identifies key barriers such as late-stage aerodynamic integration and cross-disciplinary misalignment. A generalized framework is proposed, highlighting early-stage simulation-styling fusion, multi-objective optimization, and closed-loop validation. Future directions include AI-driven design platforms, cross-sector collaboration, and sustainable aerodynamic optimization. The findings offer insights for both researchers and industry practitioners aiming to accelerate aerodynamic innovation.